Drones, tones, and timbres : sounding place among nomads of the inner Asian mountain-steppes - Pegg, Carole (University of Illinois Press, 2023)
"Based on almost thirty years of collaborative research, Carole Pegg's long-awaited study examines how the Indigenous nomadic, semi-nomadic and formerly nomadic peoples of Russia's southern Siberian republics sound multiphonies of place in a post-Soviet global world. Pegg merges ethnography, participatory experiences, Indigenous voices, and comparative scholarship to present an innovative study that echoes the tripartite structure of both the Altai-Sayan universe and the drone-partials musical model. Three interwoven strands form the underlying theoretical drone: an ontological sonicality and musicality that enables emplacement and movement; the importance of the animism-shamanism at the core of Indigenous spiritual practices to personhood, ecology, and community; and the agency of sonic performances. While demonstrating the role music practices play in both physical and spiritual embodiments and relationships, Pegg also shows how ontological musicality and the contexts in which it is embedded are essential to the identities, ways of life, and very senses of being of Indigenous nomadic Altai-Sayan peoples"--